1998
DOI: 10.1007/s002130050782
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dopamine D 3 /D 2 receptor agonists on intracranial self stimulation in the rat

Abstract: The effects of the dopamine D3/D2 receptor agonists quinpirole, quinelorane and (+/-)7-OH-DPAT [(+/-) 7-hydroxy-2(N,N-di-n-propylamino) tetralin] on intracranial self-stimulation (ICSS) were investigated. Rats implanted with bipolar electrodes into the lateral hypothalamus were trained to lever press on a continuous reinforcement schedule for positively reinforcing trains of electrical stimulation. Three measures of responding were calculated; the frequency at which responding was 50% of the maximum (M50), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…In contrast to D1 sensitivity, the C57 and DBA strain difference was more pronounced after treatment with the D2 agonist, quinpirole, and the D2 antagonist, raclopride. Quinpirole had dose-and time-dependent effects on threshold and MAX consistent with previous observations (Hatcher and Hagan, 1998;Malanga et al, 2008). In both C57 and DBA strains, quinpirole elevated threshold and suppressed MAX in the first 15 minutes after administration.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to D1 sensitivity, the C57 and DBA strain difference was more pronounced after treatment with the D2 agonist, quinpirole, and the D2 antagonist, raclopride. Quinpirole had dose-and time-dependent effects on threshold and MAX consistent with previous observations (Hatcher and Hagan, 1998;Malanga et al, 2008). In both C57 and DBA strains, quinpirole elevated threshold and suppressed MAX in the first 15 minutes after administration.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008). For example, quinpirole facilitated ICSS in some studies (Ranaldi and Beninger, 1994;Carr et al, 2001), depressed ICSS in other studies (Rady et al, 1994;Hatcher and Hagan, 1998), and produced variable effects across doses and different ICSS rates in yet other studies (Nakajima and O'Regan, 1991;Depoortere et al, 1996;Malanga et al, 2008). The variable effects of DA agonists on ICSS contrast with the more reliable selfadministration of these compounds in rats and nonhuman primates (Woolverton et al, 1984;Caine and Koob, 1993;Weed et al, 1993;Grech et al, 1996;O'Connor et al, 2011;Huskinson et al, 2014).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 70%
“…Selective D1 agonists such as SKF38393 [(6)-1-phenyl-2,3,4,5-tetrahydro-(1H)-3-benzazepine-7,8-diol hydrobromide], SKF82958 (3-allyl-6-chloro-1-phenyl-1,2,4,5-tetrahydro-3-benzazepine-7,8-diol), and A77636 [(1R,3S)-3-(1-adamantyl)-1-(aminomethyl)-3,4-dihydro-1H-isochromene-5,6-diol] have been reported to facilitate ICSS in some studies (Nakajima and O'Regan, 1991;Ranaldi and Beninger, 1994;Carr et al, 2001;Gilliss et al, 2002;Malanga et al, 2008), but the magnitude of facilitation is generally weak and may be accompanied by evidence for impaired performance, and other studies have reported only depression by D1 agonists (Hunt et al, 1994;Baldo et al, 1999). Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008). For example, quinpirole facilitated ICSS in some studies (Ranaldi and Beninger, 1994;Carr et al, 2001), depressed ICSS in other studies (Rady et al, 1994;Hatcher and Hagan, 1998), and produced variable effects across doses and different ICSS rates in yet other studies (Nakajima and O'Regan, 1991;Depoortere et al, 1996;Malanga et al, 2008).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 90%
“…Similarly, norepinephrine originating in the locus coeruleus and innervating the hippocampus, thalamus, hypothalamus, basal forebrain, olfactory nuclei, cortex, and septum has also been associated with the reinforcing effects of selfstimulation via its contribution of axons to the medial forebrain bundle (29). Interestingly, antidepressants and dopamine agonists (e.g., tricyclics), affect selfstimulation behavior in rodents (20,27). Serotonergic mechanisms are also probably involved in influencing self-stimulation behavior resulting from interactions with the dopaminergic system (26).…”
Section: Discussionmentioning
confidence: 99%